Escaping Salem : the other witch hunt of 1692 - Godbeer, Richard (New narratives in American history., 2005)
Tells the story of Kate Branch, a seventeen-year-old afflicted by strange visions and given to blood-chilling wails of pain and fright. Branch accused several women of bewitching her, two of whom were put on trial for witchcraft. This work takes us inside the courtroom - and inside the minds of the surprisingly skeptical Stamford town folk.